Peningkatan Keterampilan Perempuan Desa Ngombakan Melalui Pembuatan Pupuk Organik Cair Berbahan Dasar Limbah Industri Alkohol dan Sampah Rumah Tangga - Amelia Choya Tia Rosalia; Michael Berlito Kristian Aji; Pratama Senapati Bagus Handoko; Resah Aprianti (Jurnal Bina Desa, 2026)
The majority of the residents of Ngombakan Village are traditional alcohol craftsmen. The by-products of this production process result in waste that is harmful to the environment and is produced in significant volumes. The aim of this community service project is to reutilize the waste generated from alcohol production into valuable liquid organic fertilizer. The resulting fertilizer has been proven effective in enhancing the fertility of planting media, leading to faster germination and growth of seeds. The participants of the socialization event were 25 women from Kleco Hamlet. The community service activities included a socialization session on the production of liquid organic fertilizer, combining alcohol industry waste and household waste, and an introduction to its application on cocopeat planting media. This activity received positive responses from the participants, as indicated by their active questioning and willingness to participate in demonstrations. The outcome of this socialization was that the participants gained knowledge on the production of liquid organic fertilizer and its application in planting media in limited space.